Microbial Silver Nanoparticles Enhance the Performance of Maize Plants Cultivated in Naturally Occurring Saline Soil - Martínez, Fernando Gabriel (2026)
Soil salinity is a major abiotic stress that limits agricultural productivity worldwide. The aim of this study was to evaluate whether biogenic silver nanoparticles (AgNPs) can mitigate salt stress in maize while preserving soil biological health under realistic soil conditions. Biogenic AgNPs were synthesized using biomolecules from the actinobacterium Streptomyces sp. Z38 and characterized, confirming spherical morphology, colloidal stability, and surface functionalization. Maize plants grown under greenhouse conditions were treated with biogenic or chemically synthesized AgNPs, and plant performance, oxidative stress responses, and soil biological properties were evaluated. Under saline conditions (6 mS cm−1), biogenic AgNPs markedly improved plant growth, almost fully restoring leaf dry weight (165.08 ± 23.68 mg) to values comparable with non-saline controls (171.81 ± 15.00 mg), while chemical AgNPs induced only partial recovery. Biogenic AgNPs also enhanced antioxidant defenses, increasing catalase activity by ~15% above non-saline levels and reducing lipid peroxidation from 232.34 ± 31.74 to 102.63 ± 5.75 Eq. MDA g−1. In parallel, chlorophyll a content increased by ~29% relative to non-saline plants, indicating improved photosynthetic performance. Transmission electron microscopy of leaves confirmed AgNPs internalization, with nanoparticles primarily sequestered in vacuoles. Analyses of experimental soils showed that biogenic AgNPs enhanced microbial enzymatic activity and respiration, while chemical AgNPs had inhibitory effects. Ecotoxicological assays further indicated low soil toxicity following biogenic AgNPs plant treatment, as reflected by high lettuce germination rates. Overall, these findings highlight the potential of biogenic AgNPs obtained from actinobacteria as sustainable nanobiotechnological tools to mitigate salt stress in crops while improving soil health. Future field-scale studies will be required to validate their agronomic applicability.